Senses and urban Landscape (Journal of Planner and Development, 2020)
The city is often discussed in barren, eviscerated terms and in technical jargon by urban professionals as if it were a lifeless, detached being. In fact, it is a sensory, emotional, lived experience. How often do strategic urban plans start with the words ‘beauty’, ‘love’, ‘happiness’ or ‘excitement’, as opposed to ‘bypass’, ‘spatial outcome’ or ‘planning framework, So the research problem was formed by the weakness of the sensory perception of cities and the weakness of the sense of different spaces, which in turn leads to weakness of belonging, identity and clarity, Therefor we focus here on the sensory perception. The hypothesis Recognize Senses as helpful tool in increasing people’s understanding of different spaces and finding imaginative solutions and engaging and moving people. The aim was to draw up mechanisms to achieve a plan that communicates with the people and reflects their ideas and will (achieving belonging - continuity - building identity - and clarity), and enables the as individuals to integrate with the urban life in order to live well, which stimulates the work and the sense of place and increases the perception of the users of their spaces, and enhances the sense of collective identity of the place.